A Syntactic Analysis of Noun Phrase Structures in BBC Online News Headlines - Elwan Ridhonta Sinulingga; Firza Sakinah; M. Radja Affan Hanafie; Rosanti Nasution; Salwa Khumairah Hasyim; Siti Ismahani (Jurnal Pendidikan dan Sastra Inggris, 2026)
Syntactic analysis plays a very important role in understanding sentence structure in journalistic texts. By analyzing syntax, learners can understand how sentence elements such as phrases, clauses, and word order are arranged to form accurate meaning. The aim of this research is to conduct a syntactic analysis of noun phrase (NP) structures as they appear in BBC online news. The research subjects used in this study are six BBC news headlines related to natural disasters, which were selected and adjusted based on recent events that have attracted significant attention from various countries around the world. The results of this study show that noun phrase (NP) structures play a crucial role in conveying the main information in a concise and effective manner. Because they can present the core event, location, and severity of the disaster compactly, while also reflecting the characteristic style of journalistic language that maintain brevity and clarity.